2017
DOI: 10.5194/angeo-35-701-2017
|View full text |Cite
|
Sign up to set email alerts
|

Studying the variability in the diurnal and seasonal variations in GPS total electron content over Nigeria

Abstract: Abstract. The study of diurnal and seasonal variations in total electron content (TEC) over Nigeria has been prompted by the recent increase in the number of GPS continuously operating reference stations (CORSs) across Nigeria as well as the reduced costs of microcomputing. The GPS data engaged in this study were recorded in the year 2012 at nine stations in Nigeria located between geomagnetic latitudes -4.33 and 0.72 • N. The GPS data were used to derive GPS TEC, which was analysed for diurnal and seasonal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
(69 reference statements)
4
14
0
Order By: Relevance
“…For all seasons, premidnight (18:00-23:00 LT) values of TEC are higher than post-midnight (00:00-05:00 LT) TEC values during all years. Seasonal variation shows an asymmetry in the equinoxes and solstices in the NEI as also reported by Fayose et al (2012) and Eyelade et al (2017). Maximum OBS-TEC values in 2011 and 2012 were recorded in the September equinox.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For all seasons, premidnight (18:00-23:00 LT) values of TEC are higher than post-midnight (00:00-05:00 LT) TEC values during all years. Seasonal variation shows an asymmetry in the equinoxes and solstices in the NEI as also reported by Fayose et al (2012) and Eyelade et al (2017). Maximum OBS-TEC values in 2011 and 2012 were recorded in the September equinox.…”
Section: Discussionsupporting
confidence: 78%
“…The semi-annual variation resulting from the effect of equatorial ionization anomaly (EIA) in the ionosphere has been attributed to the effect of the solar zenith angle and magnetic field geometry (Wu et al, 2008;Rama Rao et al, 2006a). Another important feature of ionospheric parameters (known as equinoctial asymmetry), which is reported in the work of Bolaji et al (2012), Akala et al (2013), Eyelade et al (2017Eyelade et al ( ), D'ujanga et al (2017 and Aggarwal et al (2017), is clearly seen for all years used in this work. Akala et al (2013) also reported minimum and maximum seasonal VTEC values during the June solstice and December solstice respectively during the ascending phase of so-lar cycle 24.…”
Section: Methodssupporting
confidence: 59%
“…work of Bolaji et al, (2012); Akala et al, (2013); Eyelade et al, (2017);D'ujanga et al, (2017); Aggarwal et al, (2017), is clearly seen in all years used in this work. Akala et al, (2013) strong phenomenon in low latitudes (Aggarwal et al, 2017).…”
Section: Resultssupporting
confidence: 57%
“…204 Fayose et al, (2012), Okoh et al, (2014), Eyelade et al, (2017) who have explored the NEI. It can be seen that OBS-TEC is much higher in with maximum values up to TECU in March compared with IRI-2016 maximum of 54 TECU in the month of October, 2014.…”
Section: Resultsmentioning
confidence: 99%
“…The dominant mechanisms at the equatorial and low latitudes responsible for the generation of large scale TEC gradients include: the Appleton anomaly, equatorial electro jet (EEJ), Equatorial Spread F (ESF), geomagnetic storms among others [1, 2, [7][8][9]. The Appleton anomaly is as a result of the so-called fountain effect; whereby an eastward electric field at the equator gives rise to an upward ExB drift during the daytime [10]. Moreover, after the plasma is lifted to greater heights, it is able to diffuse downward along magnetic field lines under the influence of gravity and pressure gradient forces (±17 magnetic equator).…”
Section: Introductionmentioning
confidence: 99%